(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2025)
‘From the small screen to the big screen’ proclaims the advertising text of the Super8’s of a television series distributed in 1979 by the German company Piccolo Film, emphasizing the novelty and the potential of format. The film is Sandokan, an Italian miniseries from 1976 directed by Sergio Sollima and starring the Indian actor Kabir Bedi as the exotic protagonist of Salgari’s famous adventure. This contribution maps the European and global success of the series and its media format’s history, focusing in particular on Super8’s distribution. It retraces Super8 ‘reduction prints’ in different languages by relying on film catalogues from the seventies and on sources gathered from platforms such as Imdb and Ebay (where collectors trade Super8) and interviews to ex-employees and owners of former Super8’s distribution companies in Italy and Germany. The paper considers the geographical circulation of Sandokan’s Super8 editions to investigate Sandokan’s figure beyond its literary origins. Super8’s history shows an unexplored relation between media broadcasting and past practices of home viewing beyond the theatrical realm. Sandokan’s Super8 circulation can be regarded as part of larger phenomenon of consumer culture, where reduction prints become a synecdoche to a larger cultural myth.